Movement variables improving the performance in the flat versus the undulating breaststroke - Soons, B.; Colman, V.; Silva, A.; Sanders, R.; Persyn, U. (coachesinfo.com)
In a previous article, data from 62 high level swimmers were analysed to provide an indication of how variables relating the amount of undulation were correlated with the fluctuations in centre of mass velocity and performance (Soons 2001 (10), Silva et al. 2003 (9), Soons et al. 2005 (12)). The findings indicated that for the sample as a whole, and for the women separately, the more undulation the smaller the centre of mass velocity fluctuations and the better the performance. In the five most undulating style variants (all women) of this sample, 27.7% less velocity fluctuation was found than in the five flattest (all men) (Colman et al. 1998 (2)). Nevertheless, as emphasised in another previous article, one must take into account that, although women are generally physically more suited to an undulating style and men to a flat style, this cannot be generalised (Colman et al. 2005 (3)).